Lineage commitment of transformed haematopoietic progenitors is determined by the level of PKC activity. - Rossi, F (1996)
Our previous work showed that haematopoietic precursors transformed by the E26 avian leukemia virus undergo multilineage differentiation in response to the phorbol ester phorbol 12-myristate 13-acetate (PMA). Treatment of the cells with high concentrations of PMA (100 nM) favours myelomonocytic differentiation, while lower concentrations (20 nM) induce predominantly eosinophil differentiation. Here we have investigated the role of protein kinase C (PKC) in this process and found that 100 nM, but not 20 nM, PMA dramatically down-regulates total cellular PKC activity, indicating that high PMA concentrations result in less efficient signalling than lower PMA concentrations. Consistent with these findings is the observation that very low PMA concentrations (1 nM), which presumably only moderately activate PKC, induce myeloid differentiation. This suggests the existence of two PKC thresholds which play a role in lineage commitment. To test the model, alpha- and epsilon-PKC isoforms were expressed in E26-transformed progenitors. These cells exhibited myelomonocytic differentiation even in the absence of PMA, while treatment with concentrations of PMA as high as 100 nM led to the differentiation of predominantly eosinophils and failed to downregulate the exogenous PKC. Our results suggest that different levels of PKC activity result in three different phenotypes: (i) no PKC activity maintains the progenitor phenotype; (ii) low PKC activity favours myelomonocytic differentiation; (iii) high PKC favours eosinophil differentiation.